PERAN NYAMA PAT DALAM KEHIDUPAN MANUSIA PERSFEKTIF AGAMA HINDU - Gede Rai Parsua (Kalangwan Jurnal Pendidikan Agama, Bahasa dan Sastra, 2022)
The results of this study, Nyama Pat plays a very important role in human life from newborn to human death. According to Lontar Panugrahan Dalem Nyama Pat is contained in the teachings of Kanda Empat. The role of Nyama Pat or often called Kanda Empat is very instrumental in human life starting from home and in human life which reads "This is a very important teaching created by Ida Bhatara Dalem, which is called sarining kanda pat without literature. There are so many uses: when placed at home while maintaining the house and the occupants of the house. He can reject all the deeds of evil people. Everything that is harmful does not work to do evil. Everything that does evil can be rejected. After all, if you can learn to master this knowledge, it can become the essence of all mantras and reach Nirvana. When to purify oneself is achieved. When reverence for him is made a place of worship, because it can provide supernatural powers that cannot be defeated by all spells. Mantras that come from a hundred saucy lontar are defeated by the words of one saucy, said a hundred saucy lontars are defeated by one form of offering banten. One hundred varieties of Banten are subdued by one dulang sasaji.” The contents of the Panugrahan Bhatara Dalem ejection which alludes to Nyama Pat playing a very important role in human life can be used for anything in everyday life as protection and cannot be defeated by anyone, which is of course as far as humans know or To carry out these teachings, of course, by making worship so that humans can worship every day or every time needed. That is the main thing so that the teachings are not abused or disseminated to people who have no intention of knowing the teachings of Nyama Pat. When you are disciplined in carrying out this teaching, what you aspire to can be achieved and loved by the Gods. Keywords: Nyama Pat